Swallowing sounds profile of a post stroke group using electronic stethoscope software - Branco, Larissa Lopes; Cardoso, Maria Cristina de Almeida Freitas (Distúrbios da Comunicação, 2020)
Introduction: Cervical auscultation is a complementary evaluation to dysphagia clinical evaluation. Objective: To establish the swallowing sounds profile in post-stroke patients’ group. Methods: Clinical cross-sectional study, whose collection and acoustic analysis was performed through the electronic stethoscope of the Littman brand (model 4100) and clinical evaluation of dysphagia, with the collection of 45 swallows of liquids and 9 swallows dried. Results: Sample composed of nine post stroke individuals with an average age of 54.33-year-old; 55.6% of patients with swallowing disease. The frequency varies between 20-500 Hz; the dry swallowing frequencies occurred in 250 Hz in swallowing without alteration, and between 20 Hz and 249 Hz in disease. For the swallowing of liquids, between 20Hz and 249 Hz without alteration, and 250 in Hz disease. The average dry swallowing time was given in 110.3 ms (SD ± 38. 6 ms) and with liquids in 111.6 ms (SD ± 36.5 ms). The average time between the dry swallowing events was 125 ms (SD ± 54.74 ms) in swallowing without alteration and of 98.60 ms (SD ± 18. 66 ms) in disease; in liquid swallowing it was 100.20 ms (DP ± 31.01 ms) without alteration, and 120.68 ms (SD ± 38.52 ms) in the swallowing disease. Conclusion: The digital stethoscope showed itself as an instrumental possibility for the collection, but for the acoustic analysis it is not productive. The results of the dry and liquid swallowing were: average time around 110 ms and at low frequency, varying between 20 Hz and 500 Hz for both consistencies, with post stroke patients.